Sir Thomas Elyot as lexicographer - Stein, Gabriele (Oxford University Press, 2014)
Sir Thomas Elyot's Latin-English dictionary became the leading work of its kind. Gabriele Stein examines its principles, methods, and organisation, and the texts and authors Elyot used as sources. She considers the book's impact on sixteenth - and seventeenth-century dictionaries and assesses its place in Renaissance lexicography.